2000
DOI: 10.1002/(sici)1099-0518(20000615)38:12<2254::aid-pola140>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(silyl ether)s containing pendant chloromethyl groups by the polyaddition of bis(oxetane)s with dichlorosilanes

Abstract: The polyaddition of bis(3‐ethyl‐3‐oxetanylmethyl) terephthalate (BEOT) with dichlorodiphenylsilane (CPS) using tetrabutylammonium bromide (TBAB) as a catalyst proceeded under mild reaction conditions to afford a polymer containing silicon atoms in the polymer main chain. A poly(silyl ether) (P‐1) with a high molecular weight (Mn = 53,200) was obtained by the reaction of BEOT with CPS in the presence of 5 mol % of TBAB in toluene at 0 °C for 1 h and then at 50 °C for 24 h. The structure of the resulting polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Polymers containing either C−Si−O−C or C−O−Si−O−C linkages in the repeating unit have been synthesized by several methods: 1) uncatalyzed melt‐condensation of aryl‐ or biaryldiols with dianilino‐ or diphenoxysilanes; 2) reactions of dichlorosilanes with either bis(epoxide)s or bis(oxetane)s catalyzed by quaternary ammonium salts, thus resulting in polymers with reactive pendant chloromethyl groups; 3) hydrosilylation of aliphatic and aromatic ketones or benzoquinones with hydrosilanes catalyzed by ruthenium and palladium complexes; and 4) dehydrogenative coupling of alcohols with hydrosilanes catalyzed by palladium and rhodium complexes . Polysilylethers (PSEs) bearing aryl and biaryl backbones are typically solids with softening temperatures above 50 and 150 °C, respectively, whereas those bearing aliphatic backbones typically have glass‐transition temperatures ( T g ) below −80 °C .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Polymers containing either C−Si−O−C or C−O−Si−O−C linkages in the repeating unit have been synthesized by several methods: 1) uncatalyzed melt‐condensation of aryl‐ or biaryldiols with dianilino‐ or diphenoxysilanes; 2) reactions of dichlorosilanes with either bis(epoxide)s or bis(oxetane)s catalyzed by quaternary ammonium salts, thus resulting in polymers with reactive pendant chloromethyl groups; 3) hydrosilylation of aliphatic and aromatic ketones or benzoquinones with hydrosilanes catalyzed by ruthenium and palladium complexes; and 4) dehydrogenative coupling of alcohols with hydrosilanes catalyzed by palladium and rhodium complexes . Polysilylethers (PSEs) bearing aryl and biaryl backbones are typically solids with softening temperatures above 50 and 150 °C, respectively, whereas those bearing aliphatic backbones typically have glass‐transition temperatures ( T g ) below −80 °C .…”
Section: Figurementioning
confidence: 99%
“…Polysilylethers (PSEs) bearing aryl and biaryl backbones are typically solids with softening temperatures above 50 and 150 °C, respectively, whereas those bearing aliphatic backbones typically have glass‐transition temperatures ( T g ) below −80 °C . These studies have shown, as expected from the chemistry of silyl protective groups, that PSEs synthesized from secondary alcohols or from silanes bearing bulky groups (e.g., Ph) are much more resistant to either hydrolysis or methanolysis than are PSEs made from either primary alcohols or from silanes bearing unhindered groups (e.g., Me) . Most recently, polymers containing C−O−Si−O−C linkages were synthesized through silicon acetal metathesis polymerization catalyzed by a strong acid .…”
Section: Figurementioning
confidence: 99%
“…Due to the remarkable significance of this framework, the past decade witnessed significant progress toward the synthesis of poly­(silyl ether)­s. The synthetic methods are focused on polyaddition, polycondensation, and hydrosilylation polymerization . However, polyaddition and polycondensation are limited to availability of structurally diverse monomers or involve hazardous stoichiometric byproduct.…”
mentioning
confidence: 99%
“…The synthetic methods are focused on polyaddition, polycondensation, and hydrosilylation polymerization . However, polyaddition and polycondensation are limited to availability of structurally diverse monomers or involve hazardous stoichiometric byproduct. In contrast, hydrosilylation polymerization is the most atom-economic way to synthesize poly­(silyl ether)­s (Scheme a) .…”
mentioning
confidence: 99%
“…The polymers are degraded via the cleavage of the silicon–oxygen bonds with an acid, a base, or an alcohol. In most cases, poly­(silyl ether)­s and poly­(silyl ester)­s are synthesized via the polycondensation of dichlorosilanes or dihydrosilanes with difunctional alcohols, carboxylic acids, silyl esters, or ketones or the polyaddition of dichlorosilanes and bis­(cyclic ether)­s. , Polyurethanes that degrade via the desilylation of a silyl-protected phenol moiety were also synthesized via polyaddition . The step-growth mechanisms, however, complicate controlling the molecular weights and molecular weight distributions (MWDs), controlling the distances between the cleavable units without changing the structures of the monomers, and introducing cleavable silyl moieties at the desired positions.…”
mentioning
confidence: 99%